Prescribing and the core curriculum for tomorrow's doctors: BPS curriculum in clinical pharmacology and prescribing for medical students - Ross, Sarah (Blackwell Science Inc, 2012)
Prescribing is one of the commonest tasks expected of new doctors and is a complex process involving a mixture of knowledge, judgement and skills. Preparing graduates to be prescribers is one of the greatest challenges of modern undergraduate medical education and there is some evidence to suggest that training could be improved. The aims of this article are (i) to review some of the challenges of delivering effective prescribing education, (ii) to provide a clear statement of the learning outcomes in clinical pharmacology and prescribing that should be expected of all medical graduates and (iii) to describe a curriculum that might enable students to achieve these outcomes. We build on the previous curriculum recommendations of the British Pharmacological Society and take into account those of other key bodies, notably the General Medical Council. We have also reviewed relevant evidence from the literature and set our work in the context of recent trends in medical education. We divide our recommended learning objectives into four sections: principles of clinical pharmacology, essential drugs, essential therapeutic problems and prescribing skills. Although these will not necessarily be accepted universally we believe that they will help those who design and map undergraduate curricula to explore potential gaps and identify improvements.